WORKSHOP “PETANI PERKOTAAN” BERKEBUN ASYIK DENGAN HIDROPONIK - Wahyuningsih, Panca; Rahman, Faisal Riza; Kartika, Daniel Adhi; Efendi, Khusnan; Hidayat, M. Ibnu (Fokus ABDIMAS, 2024)
This community service workshop titled "Fun Farming with Hydroponics" was conducted by Dharma Wanita Persatuan of Vocational School, Diponegoro University, with the aim of introducing hydroponic farming techniques to its members. Hydroponics, a method of growing plants without soil, offers an efficient solution for urban farming, particularly in areas with limited space. The workshop began with an educational presentation on the basics of hydroponic farming, followed by a demonstration of the tools and materials required for successful hydroponic cultivation. Participants were actively engaged throughout the session, as evidenced by their enthusiasm and interactive discussions with the facilitators. They were also given the opportunity to practice assembling simple hydroponic systems and planting using the provided materials. The results of this workshop were highly positive, with participants gaining both theoretical knowledge and hands-on experience in hydroponic farming. This initiative successfully raised awareness of the importance of sustainable agriculture and its potential to enhance local food security. By empowering members of Dharma Wanita Persatuan with practical skills and knowledge, this workshop also highlighted the potential of hydroponics as a home-based economic activity. It is expected that the participants will implement these techniques in their homes and communities, contributing to wider adoption of hydroponic farming methods. Overall, the workshop served as a valuable platform for promoting environmental sustainability and self-sufficiency through innovative agricultural practices. Keywords: hydroponics, sustainable agriculture, community service, urban farming, food security, vocational education.